Symptom severity and quality of life in patients with atrial fibrillation: Psychological function outweighs clinical predictors. (15th March 2019) - Walters, Tomos E.; Wick, Kate; Tan, Gabriel; Mearns, Megan; Joseph, Stephen A.; Morton, Joseph B.; Sanders, Prashanthan; Bryant, Christina; Kistler, Peter M.; Kalman, Jonathan M.
Abstract: Background: The key drivers of symptom severity and health-related quality of life (hr-QOL) in patients with atrial fibrillation (AF) remain unclear. We aimed to determine the relative contribution to symptom severity and hr-QOL of clinical factors including left ventricular (LV) diastolic function and ventricular rate control during AF and of psychological functioning. Methods: Seventy-eight consecutive patients with symptomatic AF and preserved LV systolic function underwent detailed evaluation of i ) AF symptom severity and hr-QOL; ii ) clinical factors including left ventricular (LV) diastolic function, AF burden, and ventricular rate during AF and iii ) state and trait aspects of psychological functioning. Results: Moderate-to-severe AF-related symptoms were reported by 64% of the study population whilst 36% reported no more than mild symptoms. Worse symptom severity was associated with a higher score on the Perceived Stress Scale (16.7 ± 4.4 vs. 5.4 ± 4.4, p < 0.0001) and higher prevalence of the Type D Personality (20/50 vs. 4/28, p = 0.012). In multivariable models, only a predisposition to subjectively appraise life situations as stressful (higher PSS score) and a personality with a higher degree of negative affectivity and social inhibition (higher TDPS score) were independent predictors of higher AF symptom severity and poorer hr-QOL. No clinical factors including AF burden, ventricular rates during AF or LV diastolic function were significant predictors of AF-specific symptoms or hr-QOL. Conclusion: In a tertiary AF population with preserved LV systolic function, only psychological functioning consistently predicts both AF-related symptoms and hr-QOL. LV diastolic function, AF burden, and ventricular rate during AF are not independent predictors. Highlights: In a tertiary AF population, in analyses incorporating both clinical variables and variables of psychological function: LV diastolic function does not predict AF symptom severity or hr-QOL. Ventricular rates during AF do not predict AF symptom severity or hr-QOL. AF burden or persistence do not predict AF symptom severity or hr-QOL. Psychological function, specifically stress perception and a type D personality, is the dominant predictor of symptom severity and hr-QOL.